Abstinence Self-Efficacy and Resilience in Persons with Substance Use Disorder - L. Iris Devi; Arunjyoti Baruah; Nurnahar Ahmed (Indian Journal of Psychiatric Nursing)
Context: Substance use affects the personal, social, and familial aspects of a person’s life and is usually persistent, chronic, and relapsing in nature. Self-efficacy and resilience are important in the process of recovery of these persons. Aims: The current study aimed to examine the abstinence self-efficacy and resilience of persons with substance use disorder. Study Design: The study adopted a descriptive cross-sectional research design. Materials and Methods: Convenience sampling technique was used to select 60 patients in a tertiary mental health-care setting. The tools used were Connor–Davidson Resilience Scale and Alcohol Abstinence Self-Efficacy Scale. Results: The mean resilience was 76.52 ± 14.320 and the mean abstinence self-efficacy (confidence) was 57.50 ± 19.108. There was also a significant positive correlation between resilience and abstinence self-efficacy (confidence), r = 0.325, P = 0.011. Conclusions: The study findings indicate that patients with substance use disorder have moderate abstinence self-efficacy and resilience. Resilience and abstinence self-efficacy can be further enhanced in substance-using persons through proper interventions which will help to maintain long-term abstinence.